THE IMPORTANCE OF LEGAL RESEARCH IN PROFESSIONAL PRACTICE - Jorovlea, Elvira; Codreanu, Alina (SWorldJournal, 2025)
Legal research represents the foundation of effective professional practice, improving case preparation through identification of relevant statutes and precedents. Systematic analysis of facts in relation to law enables construction of solid arguments and